PENGARUH PELATIHAN STIMULASI DETEKSI DAN INTERVENSI DINI TUMBUH KEMBANG ANAK - Muflihah, Ima Syamrotul (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Early childhood is a critical period in child development therefore comprehensive appropriate efforts are required to grow and develop a comprehensive and qualified health care to increase children’s physical health, mental, and psychosocial health. The efforts are carried out through early detection training in child development in posyandu. The purpose of this research is to analyze the effect of early detection training on knowledge of child development and maternal skills in stimulating growth and development of toddlers in Banjarnegara district. This is a mixed methods sequential explanatory design conducted to 96 mothers with children aged 0-2 years in Banjarnegara district. The samples were divided into control group (n = 48) and intervention group (n = 48). The control group was trained on early detection of child development at mother toddler classes, while the intervention group was trained according to the stage of development of the childrens age. Assessment of knowledge and skills in stimulating maternal child growth assessed three times, before being given the training, immediately after training and one month after the training is given. The analyses were performed using unpaired t test for datas with normal distribution and Mann-Whitney test and Wilcoxon test for datas not normally distributed. The results showed that increased maternal knowledge in stimulating growth and development of infants, knowledge of appropriate developmental stages of the child's age, mother's skill in stimulating the growth and development of infants immediately after training is higher in the intervention group and decreased one month after training was lower than the control group (p<0.05). The conclusion of this research is the training on maternal age appropriate stages of child development more effective than the control group. Keywords: early detection of child development, knowledge, skills, stimulation